PELAKSANAAN PERJANJIAN WARALABA (FRANCHISEE) MAKKAN CORNDOG DI KOTA PONTIANAK - NIM. A1011191240, HARI SURYA DINATA (Jurnal Fatwa Hukum, 2025)
Abstract So it can be seen that the Makkan Corndog Franchise Giver is an individual or business entity who gives the right to utilize and/or use the Franchise he owns to the Franchisee. Franchises owned by the Franchisor. To avoid undesirable things, before being bound by a franchise agreement, each party involved must pay attention to each point in the franchise agreement carefully and thoroughly. Therefore, the franchise agreement is a very important part of the franchise business The approach method used in this research is empirical juridical. The specifications of this research are analytical descriptive. The data used in this research is primary data, namely data obtained by interviews and secondary data, namely from library materials collected through library studies, which are then analyzed qualitatively. This corndog eating franchise in the city of Pontianak has 4 outlets that have been implemented, but as we know there are still franchisees who have not yet fully implemented the terms of the agreement.However, the research also found the main obstacles in implementing re-calibration, namely lack of awareness of traders and weak law enforcement. The only sanction given to traders who do not comply with the rules is in the form of a warning, which is considered to have little deterrent effect. This lack of firmness in law enforcement influences the low awareness of traders to carry out repeat checks regularly and in accordance with applicable regulations. Keywords: Agreement, Franchise, Implementation, Abstrak Maka dapat diketahui bahwa Pemberi Waralaba Makkan Corndog adalah orang perseorangan atau badan usaha yang memberikan hak untuk memanfaatkan dan/atau menggunakan Waralaba yang dimilikinya kepada Penerima Waralaba, Penerima Waralaba adalah orang perseorangan atau badan usaha yang diberikan hak oleh Pemberi Waralaba untuk memanfaatkan dan/atau menggunakan Waralaba yang dimiliki Pemberi Waralaba. Untuk menghindari hal-hal yang tidak diinginkan, sebelum terikat oleh perjanjian waralaba, setiap pihak yang terlibat harus memperhatikan setiap poin dalam perjanjian waralaba dengan hati-hati dan saksama. Oleh karena itu, perjanjian waralaba merupakan bagian yang sangat penting dalam bisnis waralaba Metode pendekatan yang digunakan dalam penelitian ini adalah yuridis empiris. Spesifikasi penelitian ini bersifat deskriptif analitis. Data yang digunakan dalam penelitian ini adalah data primer, yaitu data yang diperoleh dengan wawancara dan data sekunder, yakni dari bahan-bahan pustaka yang dikumpulkan melalui studi kepustakaan, yang kemudian dianalisis secara kualitatif Waralaba makkan corndog di kota pontianak ini memiliki 4 oulet yang sudah dilaksanakan namun sebagaimana kita tahu masih ada penerima waralaba yang masih belum melaksanakan sepenuhnya persyaratan perjanjian tersebut Kata Kunci:Perjanjian, Waralaba, Pelaksanaan,